2019
DOI: 10.1007/s13538-019-00653-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure Anisotropy on Nonlinear Periodic Waves in a Magnetized Superthermal Electron-Positron-Ion Plasma

Abstract: The propagation properties of electrostatic cnoidal waves (periodic waves) and solitons are studied in a magnetized electron-positron-ion (EPI) plasma bearing ion pressure anisotropy and superthermality. In a two-dimensional geometry, we considered the ions to be warm having pressure anisotropy due to magnetic field. The anisotropic ions are modeled via double adiabatic Chew-Golberger-Low (CGL) theory and the lighter species (electron and positron) are following kappa distributions. A Korteweg-de Vries (KdV)-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Motivated by these events, the nonequilibrium plasmas are modelled via the nonthermal [13][14][15] or kappa type distributions. [16][17][18] This nonthermal, also known as Cairns distribution function was introduced in the ref. 13 by Cairns et al and showed that the presence of nonthermal electrons and cold ions can support the simultaneous existence of solitary waves.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by these events, the nonequilibrium plasmas are modelled via the nonthermal [13][14][15] or kappa type distributions. [16][17][18] This nonthermal, also known as Cairns distribution function was introduced in the ref. 13 by Cairns et al and showed that the presence of nonthermal electrons and cold ions can support the simultaneous existence of solitary waves.…”
Section: Introductionmentioning
confidence: 99%
“…The IA cnoidal wave structures have already been investigated in pair-ion (PI) plasma [41], electron-positron-ion (EPI) plasma [42,43] and two electrons plasma [44]. Recently, Rehman et al [45] theoretically studied the magneto-acoustic cnoidal wave structures in multi-ion plasmas, whereas Khan et al [46] investigated the effects of pressure anisotropy on IA cnoidal wave structures in a magnetized EPI plasma. The magnetosonic cnoidal waves and solitons are recently investigated in a magnetized dusty plasma [47].The authors have found the positive potential magnetosonic cnoidal and soliton structures in a magnetized dusty plasma.…”
Section: Introductionmentioning
confidence: 99%